PEMANFAATAN MEDIA CD INTERAKTIF PADA MATA DIKLAT MENGGAMBAR DENGAN PERANGKAT LUNAK (MDPL) SISWA KELAS XI SMKN 1 TILATANG KAMANG - 591-597 , Azean Kontia (CIVED, 2015)
Abstract The problem of this research is there are persistence of students who scored below the minimum completeness criteria (KKM) because the teaching methods was not well in courses Drawing With Software (MDPL). Interactive CD media utilization is expected to improve the interaction of teachers and students. Therefore, the purpose of this study is to reveal how the benefits of the Interactive CD media in teaching and learning at the SMK Negeri 1. This research uses quantitative approach to be descriptive. Subjects in this study is a class XI student of Architecture Engineering which amounted to 15 people. Technique used in data collection is observation sheets, questionnaires using Guttman scale and interview guides. The results of this research show that the use of the Interactive CD media on students of SMK Negeri 1 Tilatang Kamang included in the beneficial category because the result the average difference between the value of students before and after using the Interactive CD media increased. Data description questionnaire distributed to respondents, shows the average responses of the students are very well categorized. Keywords: Utilization, Media, Interactive CD